Aspek Hukum Keberadaan Waralaba Minimarket terhadap Toko Tradisional di Kota Medan - Chairi, Zulfi; Aflah, Aflah; Maharany, Utary (Jurnal Ilmiah Penegakan Hukum, 2019)
Modern retail activities especially minimarket franchises in Indonesia have experienced rapid development in recent years. The development of retail is certainly not separated from the economic growth of a region and also affects the economic development in the area. The purpose of this study was to analyze the legal arrangements regarding the establishment of a minimarket franchise in Medan, the impact of Medan City Guard No. 47 of 2012 concerning the Second Amendment to Medan City Regulations No. 20 of 2011 concerning Management and Development of Traditional Markets, Shopping Centers and Modern Stores, Policies that can be implemented by the Regional Government to maintain the existence of traditional shops from the mushrooming of minimarket franchises. The research used is an empirical method that uses primary data and secondary data. The results of this study indicate that in its establishment the minimarket franchise did not pay attention to socio-economic balance with the surrounding traditional shops. Juridical consequences for the issuance of Medan City Mayor Regulation (Perwal) No. 47 of 2012 concerning the Arrangement of Modern Stores on Traditional Stores is an increase in the aggressiveness of the expansion of the modern retail business to residential areas in the area. There is an unsynchronization between Pepres No. 112 of 2007 and Perwal No. 47 of 2012 which has an impact on the survival of traditional shop traders in the city of Medan.